2020
DOI: 10.1007/s13300-020-00876-0
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Induced Skin Lipohypertrophy in Type 2 Diabetes: a Multicenter Regional Survey in Southern Italy

Abstract: Introduction: Lipohypertrophies (LHs) due to incorrect insulin injection techniques have been described in the literature for decades. Their rate averages 38%, but this is still controversial because of the vast range reported by different publications, most of which fail to describe the selected detection protocol and therefore are not entirely reliable. We still need to identify the real LH rate, and only consistently using a standardized method in a large cohort of insulin-treated (IT) patients make this po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
94
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 35 publications
(97 citation statements)
references
References 43 publications
3
94
0
Order By: Relevance
“…A large body of evidence suggests that LHs are invariably associated with needle reuse and failure to rotate injection sites and are more frequent in subjects with longer diabetes duration, especially females. There is also considerable agreement in the literature regarding a strong association between LH and high SH or NSH rates, large GV, and worse HbA1c [5,7,8,[14][15][16], but not with high insulin doses. Although our results support the findings from the majority of these published reports, we found that the injection of cold insulin occurred in about 50% of patients independently of age and that it was significantly associated with rate of LHs, as if the cryo-traumas per se functioned as an add-on to repeated mechanical trauma in terms of LH-related factors.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A large body of evidence suggests that LHs are invariably associated with needle reuse and failure to rotate injection sites and are more frequent in subjects with longer diabetes duration, especially females. There is also considerable agreement in the literature regarding a strong association between LH and high SH or NSH rates, large GV, and worse HbA1c [5,7,8,[14][15][16], but not with high insulin doses. Although our results support the findings from the majority of these published reports, we found that the injection of cold insulin occurred in about 50% of patients independently of age and that it was significantly associated with rate of LHs, as if the cryo-traumas per se functioned as an add-on to repeated mechanical trauma in terms of LH-related factors.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, in past publications we have also criticized research groups unable to adopt a strict, repeatable, and safe LH identification method [8,10,11]. Even more, we have pronounced the high prevalence of LH lesions as evidence that clinicians are not sufficiently interested in this problem and have allowed patients to carry out their insulin treatment in a non-systematic and somewhat careless manner [30,31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations